Label‐Free Analysis of Cellular Biochemistry by Raman Spectroscopy and Microscopy. Issue 2 (April 2013) - Schie, Iwan W.; Huser, Thomas
Abstract: We review the biomedical applications of Raman spectroscopy at the single cell and tissue level. Raman scattering is the inelastic scattering of light by molecular bonds resulting in a wealth of spectral bands, which enable the identification of biological materials and the nondestructive analysis of dynamic changes in their biochemistry. We briefly review the basics behind highly sensitive Raman spectroscopy and highlight recent applications to biomedical research. We discuss advanced chemometrics methods that are utilized to analyze Raman spectral data and which permit one, for example, to distinguish between normal and diseased cells or which enable one to follow the differentiation of stem cells without perturbing the cellular biochemistry. We also discuss advanced coherent Raman scattering techniques, such as coherent anti‐Stokes Raman scattering and stimulated Raman scattering, which allow for the molecularly specific imaging of cells, tissues, and entire organisms in vitro and in vivo . © 2013 American Physiological Society. Compr Physiol 3:941‐956, 2013.